Laparoscopy: reasons for conversion to laparotomy in the Department of Gynecology, Institute of Polish Mother’s Memorial Hospital in Lodz in the years 2006-2012 - Żyła, Monika; Nowak, Marek; Kolasa, Dorota; Stachowiak, Grzegorz; Kostrzewa, Marta; Księżakowska-Łakoma, Kinga; R. Wilczyński, Jacek; Stetkiewicz, Tomasz (Menopause Review/Przegląd Menopauzalny, 2013)
Aim of the study: Laparoscopy is one of the most common diagnostic and therapeutic procedures in gynecology, allowing for an accurate macroscopic evaluation of abdominal and pelvic cavity with minimal invasiveness. The most common indications for gynecological laparoscopy are infertility, diagnosis and treatment of pelvic pain, ectopic pregnancy, endometriosis, adnexal inflammation, benign adnexal tumors and cysts. The aim of this study was retrospective evaluation of the causes of conversion to laparotomy procedures performed in the Department of Gynecology, Institute of Polish Mother’s Memorial Hospital in the years 2006-2012. Material and methods : The study involved 906 patients hospitalized in the Department of Gynecology ICZMP in Lodz between 2006 and 2012, who had undergone laparoscopic surgery. An analysis of 42 case records of patients in whom laparoscopy was performed initially, and then conversion to laparotomy occurred. Results : 906 laparoscopies were performed in the Department of Gynecology in the years 2006-2012. A detailed analysis of the indications for endoscopic surgery that ended in conversion to laparotomy was performed. Of all endoscopic procedures performed, in 42 cases (4.6%) the need for conversion from laparoscopy to laparotomy occurred. The most common cause was massive adhesions – in 21 cases (50%). Heavy bleeding was the reason for conversion to laparotomy in 5 patients (12%). Technical difficulties in performing laparoscopic surgery occurred in 4 women (9.5%), and difficulty to produce pneumoperitoneum in 2. In 4 patients during surgery there was damage to the intestines. The diagnosis of ovarian cancer established intraoperatively resulted in the completion of the surgery by laparotomy in 2 cases (4.8%). In other 2 patients, tumor location and its size (in both cases, tumor diameter greater than 10 cm) led to the completion of the procedure in a classical way. Conclusions : Laparoscopy is a common and generally acceptable medical diagnostic method used in the Department of Gynecology, Institute of Polish Mother’s Health Center. As with any surgical intervention, however, it involves a risk of complications, the proportion of which leads to the need for conversion to laparotomy.